Rotationally invariant periodic solutions of semilinear wave equations. (1998) - Schechter, Martin
Abstract : Under suitable conditions we are able to solve the semilinear wave equation in any dimension. We are also able to compute the essential spectrum of the linear wave operator for the rotationally invariant periodic case.